NERACA KETERSEDIAAN BERAS DI KALIMANTAN TIMUR SEBAGAI CALON IBUKOTA BARU INDONESIA DENGAN PENDEKATAN SISTEM DINAMIK - Aswan Adi; Dwi Rachmina; Y Bayu Krisnamurthi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
Rice is the main and strategic commodity in East Kalimantan Province as primary food source. Rice production in this province was relatively low, around 66.57% of its consumption need, or at 33.43% deficit in 2019. This deficit will continue to increase if East Kalimantan becomes the country's capital city in 2025 due to arrival of new residents. Therefore, a proper policy to improve the balance of rice production and consumption need should be designed. This study aimed to develop rice availability balance model and formulate policy recommendation to fullfil the rice needs in the country's capital city candidate. The method used was dynamic system approach as rice balance availability determined by supply and demand sub-system. The study results showed that the model developed could describe the rice availability balance in East Kalimantan and had good validity level. Based on the simulation results on the existing condition in 2025, the rice availability in East Kalimantan as the country's capital city was only 44.80% of the consumption need. A recommended policy scenario to improve the rice balance in this provionce is the combination of policies on production and consumption sides, namely minimal rice planting index at 1.9 (irrigation) and 1.2 (without irrigation), minimum rice yield at 4.67 tons per ha (irrigation) and 3.50 ton per ha (without irrigation), open up new rice field at 1,000 ha, no rice field conversion, conversion rate from unhusk paddy to rice yield at 64%, and maximum per capita rice consumption at 80 kg/year.